A cross-sectional study to investigate associations between flooring substrates and prevalence of limb and paw abnormalities of dogs housed in commercial breeding facilities - Stella, Judith; Gomes, Paulo; Shreyer, Traci; Croney, Candace (Frontiers in Veterinary Science, 2025)
Understanding the impact of environmental and management factors on the health and behavior of dogs housed in commercial breeding (CB) facilities is critical to their welfare. The specific aims of the study were to assess (a) associations between combinations of flooring substrates commonly used in CB kennels with foot, elbow, or hock abnormalities such as pododermatitis, calluses, or interdigital furuncle and (b) the impact of flooring substrate on dog cleanliness. Dogs (N = 373) from CB facilities (N = 20), housed on combinations of concrete, gravel, and diamond-coated expanded metal were assessed. A veterinary dermatologist examined each dog's paw, toenails, elbows, hocks, body condition, and overall cleanliness. Identified conditions included wet paws (12.6%), calluses (11.26%), erythema (6.97%), and matted paw fur (6.17%). Mixed-effects logistic regression models identified an effect of sex and wet paws (OR 6.08, CI 1.23, 29.92, p = 0.03) and age with matted paw fur (OR 1.52, CI 1.12, 2.07, p = 0.007). A few conditions were identified, including pododermatitis, hygromas, and interdigital furuncles, where management alterations might result in improved outcomes and welfare states for dogs in CB facilities.